IQBAL’S IDEAL OF DEMOCRACY AND HIS EGO PHILOSOPHY - Hakan GÜNDOĞDU (Fırat University, 2019)
In this paper, it has been attempted to show the close connection between Iqbal’s thoughts of democracy and his ego philosophy. Because that Iqbal assumes that there is a significant relationship between one’s metaphysical insights and his or her understanding of democracy, he makes an assertion that notion of democracy explained by generally referring to the western historical experience should and even can be based on the real sprit of Islam. In supporting his assertion, he attaches great importance to especially the affirmation of human self as well as such ideas as freedom, in